2017
DOI: 10.1080/19440049.2017.1323277
|View full text |Cite
|
Sign up to set email alerts
|

Sensor array for the detection of organic and inorganic contaminants in post-consumer recycled plastics for food contact

Abstract: Post-consumer recycled (PCR) plastic material is made by collecting used plastic products (e.g., bottles and other plastic packaging materials) and reprocessing them into solid-state pellets or flakes. Plastic recycling has positive environmental benefits, but may also carry potential drawbacks due to unwanted organic and inorganic contaminants. These contaminants can migrate into food packaging made from these recycled plastic materials. The purpose of this research was to identify economically viable real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Despite the amount of research on clean technologies, just one article was identified combining clean technology and plastic packaging: 'Sensor array for the detection of organic and inorganic contaminants in post-consumer recycled (PCR) plastics for food contact' (Davis et al, 2017). This document proposes to identify economically viable real-time monitoring technologies for converting recycled resin feedstocks from plastic packaging to final products, ensuring safety and quality.…”
Section: Clean Technology Scientometric Scenariomentioning
confidence: 99%
“…Despite the amount of research on clean technologies, just one article was identified combining clean technology and plastic packaging: 'Sensor array for the detection of organic and inorganic contaminants in post-consumer recycled (PCR) plastics for food contact' (Davis et al, 2017). This document proposes to identify economically viable real-time monitoring technologies for converting recycled resin feedstocks from plastic packaging to final products, ensuring safety and quality.…”
Section: Clean Technology Scientometric Scenariomentioning
confidence: 99%
“…Davis et al 50 implemented a sensor-array-based technology for the identification of inorganic and organic contaminants in PCR polymers. The technology enabled an economically viable real-time monitoring in both virgin and PCR polymer blends.…”
Section: Introductionmentioning
confidence: 99%